Faktor - Faktor Yang Mempengaruhi Audit Delay - Christine Tamba (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
The aim for this study to investigate the influence of right issue, financial leverage, audit committee education, firm performance and audit opinion on audit delay. The samples consist of listed manufactured firms from 2005 to 2009. The results show that tight issue, audit committee education, and firm leverage significantly influence on audit delay. But, audit opinion and financial leverage do not significantly influence on audit delay.Keywords : Right isisue, Leverage, Education, Performance, Audit opinion, Audit Delay